Defending Victims of Domestic Abuse who Kill : A Perspective from English Law - Mousourakis, George (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 2007)
The term “cumulative provocation” is used to describe cases involving a prolonged period of maltreatment of a person at the hands of another, which culminates in the killing of the abuser by her victim. Since the early 1990s there has been a plethora of academic commentary on the criminal law’s response to such cases. More recently, the debate has been re-opened following the publication of the English Law Commission’s proposals on the partial defences to murder. This article examines doctrinal issues that arise in relation to claims of extenuation stemming from the circumstances of cumulative provocation. It is argued that, given the scope and limitations of the provocation defence, one should view the circumstances of cumulative provocation as likely to bring about the conditions of different legal excuses. Identifying the relevant legal defence would require one to reflect on the nature of the excusing condition or conditions stemming from the circumstances of each particular case. Although the paper draws largely upon the doctrines of provocation and diminished responsibility as they operate in English law, it is hoped that the analysis offered has relevance to all systems where similar defences are recognized (or proposed to be introduced), and can make a useful contribution to the continuing moral debate that the partial excuses to murder generate.